Functions of buyers’ agent in leather exporting process: a brief analysis on the intermediary in the leather industry of Bangladesh - Bushra, Sadia (BARC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.